Friends-Enemies: Endogenous Retroviruses Are Major Transcriptional Regulators of Human DNA - Buzdin, Anton A.; Prassolov, Vladimir; Garazha, Andrew V. (Frontiers in Chemistry, 2017)
Endogenous retroviruses are mobile genetic elements hardly distinguishable from infectious, or “exogenous”, retroviruses at the time of insertion in the host DNA. Human endogenous retroviruses (HERVs) are not rare. They gave rise to multiple families of closely related mobile elements that occupy ~8% of the human genome. Together, they shape genomic regulatory landscape by providing at least ~320,000 human transcription factor binding sites (TFBS) located on ~110,000 individual HERV elements. The HERVs host as many as 155,000 mapped DNaseI hypersensitivity sites, which denote loci active in the regulation of gene expression or chromatin structure. The contemporary view of the HERVs evolutionary dynamics suggests that at the early stages after insertion, the HERV is treated by the host cells as a foreign genetic element, and is likely to be suppressed by the targeted methylation and mutations. However, at the later stages, when significant number of mutations has been already accumulated and when the retroviral genes are broken, the regulatory potential of a HERV may be released and recruited to modify the genomic balance of transcription factor binding sites. This process goes together with further accumulation and selection of mutations, which reshape the regulatory landscape of the human DNA. However, developmental reprogramming, stress or pathological conditions like cancer, inflammation and infectious diseases, can remove the blocks limiting expression and HERV-mediated host gene regulation. This, in turn, can dramatically alter the gene expression equilibrium and shift it to a newer state, thus further amplifying instability and exacerbating the stressful situation.